2007
DOI: 10.1152/ajpheart.00663.2007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SERCA isoform with faster Ca2+ transport properties improves postischemic cardiac function and Ca2+ handling and decreases myocardial infarction

Abstract: Myocardial ischemia-reperfusion (I/R) injury is associated with contractile dysfunction, arrhythmias, and myocyte death. Intracellular Ca(2+) overload with reduced activity of sarco(endo)plasmic reticulum Ca(2+)-ATPase (SERCA) is a critical mechanism of this injury. Although upregulation of SERCA function is well documented to improve postischemic cardiac function, there are conflicting reports where pharmacological inhibition of SERCA improved postischemic function. SERCA2a is the primary cardiac isoform regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 50 publications
6
69
1
3
Order By: Relevance
“…Interestingly, cardiac overexpression of SERCA1 also resulted in similar enhancement in cardiac function at baseline (37). In dystrophic muscle, the kinetics of SR Ca 2+ handling are likely depressed, potentially due to reduced SERCA activity (16)(17)(18)38).…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, cardiac overexpression of SERCA1 also resulted in similar enhancement in cardiac function at baseline (37). In dystrophic muscle, the kinetics of SR Ca 2+ handling are likely depressed, potentially due to reduced SERCA activity (16)(17)(18)38).…”
Section: Discussionmentioning
confidence: 85%
“…In vivo myocardial I/R protocol was performed as previously described with slight modifications (48). Briefly, mice were anesthetized with a mixture of intraperitoneal ketamine (55 mg/kg) and xylazine (15 mg/kg).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Triggers of apoptosis induce a caspase cascade, with caspase-3 performing a key function. Apoptosis and caspase-3 overexpression appear in the same region of the ischemic myocardial area (Talukder et al, 2007;Dow et al, 2009). Our results showed that myocardial cell apoptosis increased during the I/R process, but caspase-3 protein expression decreased in the citrate-treated groups.…”
Section: +mentioning
confidence: 52%